A Blue Photosensitizer Realizing Efficient and Stable Green Solar Cells via Color Tuning by the Electrolyte. Issue 17 (16th March 2020) - Ren, Yameng; Cao, Yiming; Zhang, Dan; Zakeeruddin, Shaik Mohammed; Hagfeldt, Anders; Wang, Peng; Grätzel, Michael
Abstract: Semitransparent dye‐sensitized solar cells (DSCs) are appealing as aesthetically pleasing and colorful see‐through photovoltaics. Green semitransparent DSCs have been presented, but the best ones rely on green zinc porphyrin photosensitizers and high volatile electrolytes. For potential outdoor applications, the zinc porphyrin DSCs employing ionic liquid electrolytes merely reached a power conversion efficiency (PCE) of 6.3% even with opaque mesoporous TiO2 films. Herein, the new green DSC is realized by using a blue organic photosensitizer in conjunction with an orange ionic‐liquid‐based electrolyte, presenting a simple and an effective path for color tuning of photovoltaics. The new approach allows for broadly modulating the color from spring green to cyan by tuning the contributions of the light absorption by the dye‐sensitized TiO2 film and the electrolyte layer. The new semitransparent DSCs with spring green to cyan colors have PCEs ranging from 6.7% to 8.1% and show stability for 1000 h under accelerated ageing test at 80 °C, superior to the zinc porphyrin DSCs. The findings pave a new way to achieve efficient and stable colorful solar cells. Abstract : A new green semitransparent dye‐sensitized solar cell (DSC) is realized by combining a blue photosensitizer with an orange electrolyte layer, which differs from the traditional method of employing a green dye. The new green DSC has superior power conversion efficiency and durability compared to conventional green zinc porphyrin sensitizers.